PENGEMBANGAN MAJALAH BERBASIS KEARIFAN LOKAL TERINTEGRASI PROFIL PELAJAR PANCASILA PADA MATERI SUHU DAN KALOR UNTUK SEKOLAH DASAR - Silvya Damayanty; Riawan Yudi Purwoko; Nur Ngazizah (Jurnal Binagogik, 2024)
This research aims to 1) produce a magazine product based on local wisdom integrated with Pancasila student profiles on temperature and heat material for elementary schools, 2) find out the feasibility of a magazine product based on local wisdom integrated with Pancasila student profiles on temperature and heat material for elementary schools. The type of research used is research and development (R&D), with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects were class V students at SDN Kembangkuning for the 2022/2023 academic year. The data collection techniques and instruments used were observation, interviews, test sheets and questionnaires. The results of research and development in the form of product validity obtained an average score of 3.71 with a classification of "very valid". The practicality analysis at the limited trial stage obtained an average of 3.71 with the classification "very practical", while the extensive trial obtained an average of 3.79 with the classification "very practical". Gain score analysis through a one group pretest posttest design obtained a score of 0.72 with a "high" interpretation, while in character observation analysis obtained a score of 3.02 at meeting I and experienced an increase at meeting II by obtaining a score of 3.5. Referring to the analysis data, it can be concluded that the local wisdom-based magazine integrated with Pancasila student profiles on temperature and heat material for elementary schools is suitable as teaching material. Thus, the cypress magazine based on local wisdom integrated with Pancasila student profiles can be used as supporting teaching material in the learning process in class V of elementary schools.